Changes in Holocene relative sea-level and coastal morphology: A study of a raised beach ridge system on Samsø, southwest Scandinavia. (September 2015) - Hede, Mikkel U; Sander, Lasse; Clemmensen, Lars B; Kroon, Aart; Pejrup, Morten; Nielsen, Lars
Changes in relative sea-level (RSL) during the Holocene are reconstructed based on ground-penetrating radar (GPR) data collected across a raised beach ridge system on the island of Samsø, Denmark. The internal architecture of the beach ridge and swale deposits is divided into characteristic radar facies. We identify downlap points interpreted to mark the transition from the beachface to the upper shoreface and, thus, sea-level at the time of deposition. This new data set shows that beach steps can be preserved and resolved in GPR reflection data. This is important, as downlap points identified at the base of the beach steps should be corrected for beach step height in order to be used as a marker of sea-level. Identification of beach steps in combination with observed changes in dips of the interpreted beachface reflections can give information about changes in the morphodynamic conditions of beach ridge progradation through time. The vertical levels of identified downlap points are combined with an age model based on optically stimulated luminescence-dated samples to reconstruct RSL for the past c. 5000 years. Overall, the reconstruction shows that the period between c. 4800 and 3800 yr BP was characterized by relatively high RSL values around 2.3 m above DVR90 (Danish Vertical Reference 1990). A marked decrease in RSL of c. 1.3 m occurred between c. 3800 and 3600 yr BP at a rate of c. 5 mm/yr. After c. 3500 yr BP, the RSL curve shows a gradual decrease at a rate of c. 0.6 mm/yr.